On the Swiss PISA 2015 sample. An external validation of core sample characteristics - Verner, Martin; Erzinger, Andrea B.; Fässler, Ursina (Swiss Journal of Educational Research, 2019)
International educational assessments do not focus on individual performance assessments, but rather make inferences about populations. For practical reasons, student samples are drawn. In order to allow valid conclusions about populations on the basis of samples, methodologically appropriate drawing and weighting procedures are necessary. Using PISA 2015 as an example, the text at hand illustrates quality characteristics of scientific random samples. Besides, the sampling procedure used in Switzerland is described. In addition, it will be examined to what extent the Swiss sample for PISA 2015 adequately depicts population characteristics, such as school programmes or the migration background and other spoken languages. The analyses support the validity of the Swiss sample for PISA 2015.